(untitled) (Journal Of Educational and Psychological Researches, 2016)
Iraqi EFL college instructors, who supervise the teaching practice of EFL student teachers, commonly experience the inefficient teaching performance of prospective teachers. This inefficiency is usually due to their inability to make connections between the practical experience and the theoretical knowledge of TEFL. One of the reasons behind this inability may be the employment of traditional ways of training and instructing student teachers. Moreover, it is usually noticed that many Iraqi EFL student teachers have a negative attitude toward the teaching profession. They explicitly state that they would join the teaching force only if they fail to work in any other field. The issue of developing EFL student teachers preparation by providing effective training strategy to prepare teachers to teach in more challenging ways is the main concern of this experimental study in which two groups are involved (experimental and control). It aims at finding out the effect of employing a cooperative learning strategy in training EFL student teachers on developing their teaching performance as well as their attitude toward teaching.